Connecting social and environmental policy in Australia: Collateral gains or collateral damage?. Issue 1 (8th August 2018) - Marston, Greg; Stark, Alastair; Matthews, Tony; Baker, Douglas
Abstract: Climate change research relating to "co‐benefits" suggests that the facilitation of social‐welfare outcomes through environmental policy offers a powerful means of incentivising climate change action. Concerns about social‐welfare, however, are often used to undermine climate change policies, typically through political claims that low‐to‐middle‐income households should not shoulder the costs of greater policy alignment between social and environmental objectives. Integrating the social into the environmental can therefore, on the one hand, lead to "co‐benefits" as each agenda promotes the other in political discourse, or alternatively to collateral damage if the policy objectives are framed as incompatible. This article explores both scenarios through two case studies of energy policy in Australia. The findings show that social‐welfare concerns can be a powerful discursive tool with the potential to facilitate political consensus, but also that this potential is not being fully realised, primarily because environmental concerns suffer when attempts are made to integrate the two areas discursively. Abstract : This article uses a policy case study approach to explore how social and environmental discourses can be better integrated in Australia, rather than constructed as being at cross‐purposes in political debates about the costs and benefits of addressing climate change.